Antioxidant Activity Study of Zingiber Zerumbet Rhizome Extract and Fraction - Haeria Doloking; Mukhriani; Rima Amalia; Andri Anugrah Pratama (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2022)
Zingiber zerumbet is a member of the Zingiberaceae family with known pharmacological potentials. This study aims to characterize the phytochemical elements and evaluate the antioxidant potential of the methanol extract, soluble ethyl acetate, and n-hexane-soluble fractions of Zingiber zerumbet rhizome. Identify secondary metabolites for the alkaloids, saponins, flavonoids, polyphenols, tannins, and steroids/triterpenoids using the chemical reaction method in test tubes. Antioxidant activity was determined based on DPPH absorbance measurements using UV-Vis Spectrophotometry. The methanolic extract contained alkaloids, flavonoids, polyphenols/tannins, steroids, and triterpenoids. The ethyl acetate soluble fraction contained flavonoids and polyphenols/tannins, and the n-hexane soluble fraction contained alkaloids and flavonoids. The free radical scavenging activities of ascorbic acid, methanol extract, ethyl acetate, and the n-hexane soluble fraction were 7.79; 100,956; 69,476, and 77,780 ppm, respectively. The findings indicated that the methanolic extract, ethyl acetate, and n-hexane soluble fraction were suitable sources of natural antioxidants.